2015
DOI: 10.3748/wjg.v21.i15.4564
|View full text |Cite
|
Sign up to set email alerts
|

MiR-19a promotes epithelial-mesenchymal transition through PI3K/AKT pathway in gastric cancer

Abstract: It has been reported that miR-19a was up-regulated in gastric cancer (GC), playing an oncogenic role. However, the underlying mechanism is still unknown. Therefore, in our present study, we investigated the role of miR-19a in gastric tissues as well as 2 GC cell lines. In vivo in clinical tissue level, we have detected basal expression level of miR-19a using real-time reversal transcriptional PCR (RT-PCR); in addition, the relevance between expression of miR-19a and clinic-pathological information was also ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 36 publications
2
48
0
Order By: Relevance
“…Zhang et al reported that Wnt5a, through stimulation of the non-classical Wnt signaling pathway, mediates EMT during the metastasis of cancer cells, and may serve as a target for the inhibition of EMT and gastric cancer metastasis (32). Lu et al have shown that miRNA-19a, which is associated with cancer invasion and metastasis and is expressed highly in gastric cancer cell lines, induces EMT in gastric cancer cells by activating the PI3K/AKT signal pathway (33 (12). Previous study by Nam and colleagues on cancer cell EMT has shown that Sp1 plays crucial roles in the integrin α5-dependent induction of EMT and metastasis (8).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al reported that Wnt5a, through stimulation of the non-classical Wnt signaling pathway, mediates EMT during the metastasis of cancer cells, and may serve as a target for the inhibition of EMT and gastric cancer metastasis (32). Lu et al have shown that miRNA-19a, which is associated with cancer invasion and metastasis and is expressed highly in gastric cancer cell lines, induces EMT in gastric cancer cells by activating the PI3K/AKT signal pathway (33 (12). Previous study by Nam and colleagues on cancer cell EMT has shown that Sp1 plays crucial roles in the integrin α5-dependent induction of EMT and metastasis (8).…”
Section: Discussionmentioning
confidence: 99%
“…The proinvasive and prometastasis effects of sorafenib (antiangiogenic agent that inhibits tumor growth but promotes tumor invasion and metastasis in HCC) were assigned to activate PI3K/Akt/snail pathway (45). Overexpression of miR19a was also shown to activate PI3K/AKT signaling, and induced EMT in gastric cancers (43). Overexpression of mortalin was earlier shown to inactivate p53, activate telomerase, and antiapoptotic signaling through Raf/MEK/ERK pathway and inhibition of conformational change of Bax (17,18,38), and to mediate erythropoietin-induced growth of erythroid progenitor cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4). PI3K-Akt signaling has been reported to regulate EMT through the transcription factor snail, a critical EMT mediator (43,44). The proinvasive and prometastasis effects of sorafenib (antiangiogenic agent that inhibits tumor growth but promotes tumor invasion and metastasis in HCC) were assigned to activate PI3K/Akt/snail pathway (45).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the present study is the first to provide evidence that PITX1 expression is modulated through miR-19a-3p in GC. miR-19a is frequently overexpressed, promotes cell proliferation and the epithelial to mesenchymal transition, and inhibits cell apoptosis in lung carcinoma [36,37], osteosarcoma stem cells [38], colorectal cancer [39][40][41][42], cell renal cell carcinoma [43], oral squamous cell carcinoma [44], hepatocellular carcinoma cells [45], pancreatic cancer [46], GC [47,48], cholangiocarcinoma [49], breast cancer [50], bladder cancer [51], medulloblastoma [52], and cervical carcinoma [53]. Our findings are consistent with these data because they provide evidence that miR19a is a key regulator of the multistep processes of cancer development.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%